Field evaluation of paralympic athletes in selected sports: Implications for training - Bernardi, M.; Guerra, E.; Di Giacinto, B.; Di Cesare, A.; Castellano, V.; Bhambhani, Y. (Medicine & Science in Sports & Exercise, 2010)
The purpose of this study was 1) to describe the acute cardiorespiratory and metabolic responses of Paralympic athletes participating in the following five sports: Nordic sit skiing (NS, n = 5), wheelchair distance racing (WR, n = 6), wheelchair basketball (WB, n = 13), wheelchair fencing (WF, n = 6), and wheelchair tennis (WT, n = 4); and 2) to examine the relationship between field test performance and laboratory measures of aerobic fitness of these Paralympic athletes.